The Religious Psychology of Children and Adolescents in Relation to Religious Counseling Programs and Strategies - Reri syafitri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The focus of this research is on the religious psychology of children and adolescents in relation to religious counseling programs and strategies. The research model employed is a literature review that examines the religious psychology of children and adolescents in connection with religious counseling programs and strategies.